Fine Particulate matter (PM2.5) is a risk factor for dermatitis by promoting the expression of thymic stromal lymphopoietin (TSLP) in keratinocytes - Fei Li; Yongpin Dong; Chunya Ni; Haidong Kan; Shuxian Yan (Wolters Kluwer Medknow Publications, 2020)
Aim: Common indoor pollutants, as fine particulate matter (PM2.5), can damage people's health and cause skin allergies. However, it remains unknown which common pollutants can lead to allergy, such as, in children atopic dermatitis, and what is the key molecule. This study aimed to investigate the thymic stromal lymphopoietin (TSLP) produced from keratinocytes after environmental pollutant stimulation. Methods: PAM212 cells were treated by several pollutants, including PM2.5, formaldehyde, m-xylene, and 1,2,4-trimethylbenzene, and tried to analyze their relationships. The mRNA expression level of TSLP was determined by qPCR. The protein level of TSLP was detected by ELISA analysis. Results: The mRNA expression of TSLP was significantly up-regulated when PAM212 cells were stimulated by PM2.5 at 25 μg/ml for 12 h. Meanwhile, the protein level of TSLP in culture supernatant was increased. However, TSLP protein production was not detected in culture supernatant treated with formaldehyde, m-xylene, and 1, 2, 4-trimethylbenzene. Conclusion: PM2.5 promotes the expression of TSLP and may aggravate allergic response using this pathway.